The First States in Central Asia and The History of Their Formation (In the Example of The Bronze Age Pottery Culture of North Bactria) (In the Example of Local Research In 1991-2022) - Komil Yunusxanovich Akhmedov (Academia One Publishing, 2023)
this article provides information on the emergence of the first statehoods in Central Asia and the history of their formation on the example of the Bronze Age pottery culture of northern Bactria
Keywords: Bronze Age; ceramics; Avesta; archaeologists